Minería de textos y datos e Inteligencia Artificial: nuevas excepciones al derecho de autor - Izquierdo, H. Andrés (2021)
There is growing attention and discussion on how national laws or international agreements should allow or prevent the fundamental right to research through text and data mining, and artificial intelligence. This article examines how copyright laws are beginning to regulate the subject matter. The most recent legislative amendments cover the inclusion of new exceptions and limitations in the rules of reproduction, storage, and public communication of works.The analysis indicates that the standards adopted or used to regulate text and data mining (TDM) vary in their content and purpose from one country to another, which begins to generate a varied, inadequate, and incompatible international environment for project development based in text and data mining and artificial intelligence. The article concludes with some thoughts regarding the right of research, artificial intelligence, data and text mining, and the creation of new limitations and exceptions to copyright law.